Dexia, ou la faillite d’une régulation du crédit local par le marché - Edoardo Ferlazzo (Revue de la Régulation)
Caught in the torment of the 2008 and the 2011 financial crises, Dexia, the historical lender to local government, was saved from bankruptcy by the Belgian and French states late in 2011. The paper looks back on the genesis of this rescue by developing an historical and institutionalist perspective of changes in local government borrowing and its regulation by the state. It sheds light on the changeover from administered regulation – where central government as from the 1950s strictly shaped supply and demand for credit in its own interest – to market-based regulation – when the state withdrew from local government lending in the 1980s. Once state-controlled, Dexia was privatized in 1993 and embarked on a strategy directed at the financial markets. That strategy collapsed in 2008, requiring state intervention of last resort to avoid contagion spreading to the financial system and a credit crunch for local government. Having created market-based regulation of local government borrowing in the 1980s, it was left to the state to “foot the bill” for the excesses of market regulation.